Low carbon investing - Elias, Jaan; Goetzmann, William N.; Rouwenhorst, K. Geert ([London] : SAGE, 2016)
In August of 2014, the movement to divest fossil fuel investments from endowment portfolios was sweeping campuses across the United States, including Gifford Pinchot State University (GPSU). How should GPSU and its investment partner Commonfund react?
Originally Published in: Elias, J., Goetzmann, W., & Rouwenhorst, K. G. (2014). Low Carbon Investing. 14-017. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://vol11.cases.som.yale.edu/low-carbon-investing.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Investments -- Moral and ethical aspects -- Case studies; Social responsibility of business -- Case studies; Nonprofit organizations -- Finance -- Case studies; Carbon dioxide mitigation -- Case studies